Konsep Pendidikan Seumur Hidup dalam Pendidikan Islam Perspektif Ibnu Khaldun - Desy Qonitah; Keysha Putri Shafa Az Zahra; Moh. Faizin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study discusses the concept of lifelong education from an Islamic perspective by highlighting the thoughts of Ibn Khaldun as a prominent figure in the history of education. Using a qualitative method based on a literature study, this research examines sources from the Qur’an, Hadith, and related scholarly works to understand the theological and philosophical foundations of lifelong education. The findings indicate that education in Islam is viewed as a continuous process that takes place from birth until the end of life. Ibn Khaldun emphasized the importance of a gradual and systematic learning process, as well as the use of methods that align with learners’ developmental stages. This concept is consistent with the demands of modern education, which emphasize active, creative, and adaptive learning. Furthermore, the study highlights various forms of lifelong education implementation, such as vocational, professional, civic, and cultural education. These findings affirm that lifelong education is an essential necessity in responding to social, technological, and civilizational dynamics, while also constituting an act of worship and a human responsibility as khalifah (stewards) on earth.